Perception of The B40 Group Quality of Life Toward Public Housing Provided by The Government of Malaysia in Langkawi - Din, Adam (2022)
Public housing infrastructure for B40 categories in Malaysia plays a significant role on the quality-of-life improvement, and the present study has configured detail B40 perception assessment on the product quality, financial benefits, facilities, environment and community development as exogenous variables. There were five predictors hypothesized on the causal effect relationship model on the B40 toward quality-of-life improvement as endogenous variables. Public Choice Theory, New Public Management and Means End Chain Theory were employed as underpinning of the hypothesized model of B40 quality of life improvement. This research also examined government support as moderating variables, and wealth creation as mediating variables on the relationship between product quality, financial benefits, facilities, environment, community development and quality of life improvement. Simple random sampling of B40 population in Langkawi Island of Malaysia were involved on the survey and there were 230 samples were gathered and analyzed. An advanced quantitative analysis using SPSS has examined, validated and established a fundamental model of B40 toward quality-of- life improvement using public housing infrastructure in Malaysia. This research found product quality, financial benefits, facilities, environment and community development of public housing significantly contributed to the B40 toward quality-of-life improvement, significantly mediated by wealth creation as well as moderated by government support. A push moderation effect of government support on the final structural model confirmed a domination of government support importance on the B40 toward quality-of-life improvement through public housing infrastructure. A final hypothesized model and validated items contributed as a role model to the stakeholders, decision makers, and public policy practitioners as well as body of knowledge. Overall, the present study fundamentally contributed to the model establishment with detail measurement of The Keluarga Malaysia (Malaysian Family), which validated through the perspective of public housing, with domination of product quality, financial benefits, facilities, environment, community development, wealth creation, government support toward the quality of life.